PENGARUH LOCUS OF CONTROL DAN KOMPETENSI PROFESIONAL MELALUI SUASANA KERJA SEBAGAI VARIABEL INTERVENING TERHADAP KINERJA GURU SMP NEGERI DI KECAMATAN PAUH KOTA PADANG - Anandari, Febrina; Veri, Jhon; Zefriyenni, Zefriyenni (Jurnal Daya Saing, 2026)
This study aims his study aims to analyze the influence of Locus of Control and Professional Competence on teacher performance with Work Atmosphere as an intervening variable in junior high schools in Pauh District, Padang City. This study uses a quantitative approach with a survey method. Data were collected through questionnaires distributed to 88 respondents, then analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method through the SmartPLS application. The results showed that Locus of Control has a positive and significant effect on Work Atmosphere, and Professional Competence also has a positive and significant effect on Work Atmosphere. Locus of Control does not affect teacher performance, while Professional Competence has a positive and significant effect on teacher performance directly. Work Atmosphere has a positive and significant effect on teacher performance. Furthermore, Work Atmosphere is able to significantly mediate the effect of Locus of Control on teacher performance and mediate the effect of Professional Competence on teacher performance. These findings indicate that improving teacher performance is not only directly influenced by professional competence but also highly depends on the level of Work Atmosphere that is formed. Locus of Control and Professional Competence through an effective work atmosphere improve performance. Therefore, schools need to strengthen the quality of the work atmosphere and build a system so that Professional Competence can improve the Work Atmosphere in order to optimize teacher performance